Comparison of NNA Agar Culture and Selective Broth Culture for Detection of Group B Streptococcal Colonization in Women - Dunne, W. Michael (American Society for Microbiology, 1998)
In 1996, the Centers for Disease Control and Prevention recommended the use of a selective broth culture for the improved detection of genital tract or anorectal carriage of group B streptococci (GBS) in pregnant women. In order to verify this recommendation in our laboratory, we compared the sensitivity of Todd-Hewitt medium with gentamicin and nalidixic acid (SBM) with our current method of direct plating on blood agar medium containing neomycin and nalidixic acid (NNA). Five hundred consecutive cervicovaginal and anorectal specimens submitted for GBS culture were included in the study. Swabs were plated onto NNA and the swabs were immersed in SBM, followed by overnight incubation at 35°C. On the following day, the NNA plates were examined for colonies typical of GBS and the organisms were identified by the CAMP test or by latex agglutination. SBM cultures were subcultured onto blood agar and CNA agar plates, and the plates were reincubated for 24 h. Negative specimens from either medium were incubated for an additional 24 h and were examined again before finalization of the results. GBS were recovered from 78 specimens by both methods; from SBM only for 17 specimens (sensitivity, 86%) and from NNA only for 16 specimens (sensitivity, 85%). A moderate to heavy growth of Enterococcus faecalis was observed on plates containing NNA-positive, SBM-negative specimens. Competitive growth studies suggested that E. faecalis suppressed the growth potential of GBS in SBM. Our study suggests that direct plating on NNA, as a single method, is equivalent in sensitivity to SBM for the recovery of GBS, and the results are often available 24 h sooner. However, it appears that both direct plating and selective broth amplification techniques are required for the maximum level of identification of colonization with GBS in pregnant women.